Dreams and Time. A Phenomenological Analysis - Crina GRIGORESCU (Studia Universitatis Babeș-Bolyai. Philosophia, 2024)
Dreams are a complex phenomenon which the philosophical field knows very little about. However, scientists like Freud or Jung, were able to prove that dream interpretation brings different advantages to our lives. For that reason, the purpose of this paper is to demonstrate that dreams, when understood, can offer us a new life perspective, especially in difficult times. Therefore, with the help of an innovative phenomenological approach introduced by Maria Zambrano, which focuses on the form of the dream and its relation with time perception, rather than the dream content, we are going to observe that people have many types of consciousness, as well as different forms of access to time which relate to multiple perception modes and emotional states. Applying this theory, Maria J. Neves, is able to demonstrate that a phenomenological dream analysis can produce significant changes in peoples’ lives.